The influence of Simvastatin carried by Chitosan nanoparticle on bone regeneration using Masson’s Trichrome histochemical stain - Muna A Alsaeed; Nada MH Al-Ghaban; Adnan karaibrahimoğlu (Journal of Baghdad College of Dentistry, 2023)
Background: Due to the complicated and time-consuming physiological procedure of bone healing, certain graft materials have been frequently used to enhance the reconstruction of the normal bone architecture. However, owing to the limitations of these graft materials, some pharmaceutical alternatives are considered instead.  Chitosan is a biopolymer with many distinguishing characteristics that make it one of the best materials to be used as a drug delivery system for simvastatin. Simvastatin is a cholesterol lowering drug, and an influencer in bone formation process, because it stimulates osteoblasts differentiation, bone morphogenic protein 2, and vascular endothelial growth factor. Objectives: histological, histochemical and histomorphometrical analyses were carried out to evaluate the  effect of local application of chitosan simvastatin nanoparticles (ChSimN) on bone healing. Materials and Methods: New Zealand rabbits (n=14) were used in this study.  Two defects were made: one on the right side (the experimental side) that received ChSimN and the other one on the left side (the control side), which left to heal spontaneously. Seven rabbits were sacrificed after 2 weeks of the experiments, while the others after 4 weeks.  Bone samples were taken for histological and histomorphometric study after the sacrifice. Results: The histological study, using both H&E and Masson’s Trichrome stain, revealed that the ChSimN group recorded an increased amount of bone formation at both time points. Histomorphometrical analysis recorded a significant increment in bone marrow and trabecular areas in the ChSimN group. Conclusion: ChSimN had a pronounced effect on bone formation.